Nonlinear Distortion in Wireless Systems : Modeling and Simulation with Matlab. - Gharaibeh, Khaled M. (John Wiley & Sons, 2011)
This book covers the principles of modeling and simulation of nonlinear distortion in wireless communication systems with MATLAB® simulations and techniques In this book, the author describes the principles of modeling and simulation of nonlinear distortion in single and multichannel wireless communication systems using both deterministic and stochastic signals. Models and simulation methods of nonlinear amplifiers explain in detail how to analyze and evaluate the performance of data communication links under nonlinear amplification. The book addresses the analysis of nonlinear system.